PENGARUH MOTIVASI BELAJAR DAN PERHATIAN ORANG TUA TERHADAP HASIL BELAJAR EKONOMI PADA SISWA KELAS XI IPS SMA NEGERI 5 PONTIANAK - Novi Andriani; Achmadi Achmadi; Husni Syahrudin (Universitas Tanjungpura, 2021)
AbstractThis study aims to determine: (1) the effect of learning motivation on economic learningoutcomes in class XI students of SMA Negeri 5 Pontianak; (2) The Effect of ParentalAttention on Economic Learning Outcomes in class XI students of SMA Negeri 5Pontianak; (3) The Influence of Parents on Economic Learning Outcomes in class XI SMANegeri 5 Pontianak.The subjects of this study were 64 students. The data collectiontechnique used a questionnaire/questionnaire and documentation.. The data analysistechnique used is the classical assumption technique and multiple regression technique.Prior to data analysis, the analysis requirements were tested including normality test,multicollinearity test, heteroscedasticity test and autocorrelation test. Hypothesis testconsists of multiple regression, F test and T test. The results of the study concluded: (1)There is an influence of learning motivation on economic learning outcomes in class XIstudents of SMA Negeri 5 Pontianak. (2) There is an effect of parental attention oneconomic learning outcomes in class XI students of SMA Negeri 5 Pontianak. (3) Learningmotivation has a positive and significant effect on economic learning outcome.Keywords: Learning Motivation, Parents' Attention, Economic Learning Outcomes